Comparative Analysis of Prothrombin Complex Concentrate and Fresh Frozen Plasma in Coronary Surgery - Biancari Fausto; Ruggieri Vito G.; Perrotti Andrea; Gherli Riccardo; Demal Till; Franzese Ilaria; Dalén Magnus; Santarpino Giuseppe; Rubino Antonino S.; Maselli Daniele; Salsano Antonio; Nicolini Francesco; et al. (Blackwell Science Asia, 2022)
Background
Recent studies suggested that prothrombin complex concentrate (PCC) might be more effective than fresh frozen plasma (FFP) to reduce red blood cell (RBC) transfusion requirement after cardiac surgery.
Methods
This is a comparative analysis of 416 patients who received FFP postoperatively and 119 patients who received PCC with or without FFP after isolated coronary artery bypass grafting (CABG).
Results
Mixed-effects regression analyses adjusted for multiple covariates and participating centres showed that PCC significantly decreased RBC transfusion (67.2% vs. 87.5%, adjusted OR 0.319, 95%CI 0.136–0.752) and platelet transfusion requirements (11.8% vs. 45.2%, adjusted OR 0.238, 95%CI 0.097–0.566) compared with FFP. The PCC cohort received a mean of 2.7 ± 3.7 (median, 2.0, IQR 4) units of RBC and the FFP cohort received a mean of 4.9 ± 6.3 (median, 3.0, IQR 4) units of RBC (adjusted coefficient, −1.926, 95%CI −3.357–0.494). The use of PCC increased the risk of KDIGO (Kidney Disease: Improving Global Outcomes) acute kidney injury (41.4% vs. 28.2%, adjusted OR 2.300, 1.203–4.400), but not of KDIGO acute kidney injury stage 3 (6.0% vs. 8.0%, OR 0.850, 95%CI 0.258–2.796) when compared with the FFP cohort.
Conclusions
These results suggest that the use of PCC compared with FFP may reduce the need of blood transfusion after CABG.